Pengembangan Lembar Kerja Peserta Didik (LKPD) Berorientasi Pendekatan Kontekstual Pada Materi Penyesuaian Diri Makhluk Hidup Terhadap Lingkungannya Untuk Kelas VI - Candra Melati Putra; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
This study aims to develop LKPD oriented contextual approach to the material adaptation of living things to their environment class VI and to describe the feasibility and responses of users (teachers and students). The research was conducted at SDN Muara Kuis  Muratara in  class  VI.  This  research is  a  research and  development research with  the  Four  D  (4D)  model. The object  of  this  research is  LKPD with contextual approach orientation. The research stages are define, design, develop and disseminate. The instrument used is a feasibility test questionnaire and teacher interviews and student questionnaires. The feasibility test was carried out by 6 validators, namely 2 material experts, 2 language experts and 2 display experts. The user response test was carried out on 15 grade VI students and 1 teacher at SDN Muara Kuis Muratara. Data analysis used percentage technique and processed descriptively. The contextual elements in the LKPD are relating (connecting), experiencing (experience), applying (application), cooperating (working together), and transfering (moving). The results of the LKPD feasibility test are contextually oriented by  the  validator in  terms  of  material aspects, language aspects  and  presentation aspects. Feasibility of the material obtained 0.81 (very feasible), language 0.66 (feasible criteria), display 0.80 (very feasible). The results of the test using the LKPD oriented contextual approach, a response was obtained that the LKPD had met the needs of teachers to be used as teaching materials to support science learning in class VI and received positive criteria by students on aspects of LKPD material quality, LKPD display  aspects,  aspects  of  material  presentation,  and  aspects  of  LKPD.  benefits through  the  distribution  of  questionnaires.  It  can  be  concluded  that  the  use  of contextual approach-oriented LKPD is feasible and positive to be used as teaching material in grade VI SD.